2009
DOI: 10.1186/1471-5945-9-12
|View full text |Cite
|
Sign up to set email alerts
|

A new two-phase dimeticone pediculicide shows high efficacy in a comparative bioassay

Abstract: BackgroundDimeticones kill head lice by physical means. Here we assessed in a comparative bioassay the ex vivo efficacy of "NYDA® sensitiv", a new two-phase dimeticone-based pediculicide similar to a product established on the market, but without fragrances.MethodsWe compared efficacy of the new product to a positive dimeticone control group, a sample of four other insecticidal and natural head lice products marketed in Germany, and an untreated control. In a bioassay, lice were exposed ex vivo to products and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
(42 reference statements)
1
11
0
1
Order By: Relevance
“…Of these types of products, dimeticone-based antilouse products (silicone oils) have attracted a good amount of attention because of their low mammalian toxicity, novel modes of action that are not neurotoxic and the possibility that they will have a low potential for the development of resistance (Heukelbach et al 2009). …”
mentioning
confidence: 99%
“…Of these types of products, dimeticone-based antilouse products (silicone oils) have attracted a good amount of attention because of their low mammalian toxicity, novel modes of action that are not neurotoxic and the possibility that they will have a low potential for the development of resistance (Heukelbach et al 2009). …”
mentioning
confidence: 99%
“…Regarding Duo LP Pro®, a controlled clinical study (Militao de Sousa et al 2009) and an ex vivo experiment with Liberalice® (Duo LP Pro®) (Heukenbach et al 2009) were conducted. However, in the latter study, the authors observed that Liberalice® was less effective, but they did not expose the lice for 8 h as it is asked in the manufacturer's instructions.…”
Section: Discussion Per Productmentioning
confidence: 99%
“…Bereits nach fünf Minuten und an allen weiteren Untersuchungszeitpunkten zeigten alle Läuse keine wesentlichen Lebenszeichen mehr, was von keiner der Vergleichssubstanzen bzw. -zubereitungen (0,5 % Permethrin, 4 % Dimeticon, Soja-Kokosnussöl, 0,3 % Pyrethrumextrakt) erreicht wurde [31,32]. Auch in der abtötenden Wirkung war das Medizinprodukt den Vergleichssubstanzen überlegen: Nach einer Inkubationszeit von nur einer Stunde betrug die Schlupfrate bei jungen Eiern 0 % und bei reifen Eiern 3,9 %, während die Schlupfraten bei den Vergleichssubstanzen mindestens bei 35 % lagen [33].…”
Section: Pediculosis Capitisunclassified